2006
DOI: 10.1111/j.1365-2966.2006.10714.x
|View full text |Cite
|
Sign up to set email alerts
|

A search for distant radio galaxies from SUMSS and NVSS - III. Radio spectral energy distributions and the z-  correlation

Abstract: This is the third in a series of papers that present observations and results for a sample of 76 ultrasteep‐spectrum radio sources designed to find galaxies at high redshift. Here we present multifrequency radio observations, from the Australia Telescope Compact Array, for a subset of 37 galaxies from the sample. Matched resolution observations at 2.3, 4.8 and 6.2 GHz are presented for all galaxies, with the z < 2 galaxies additionally observed at 8.6 and 18 GHz. New angular size constraints are reported for 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 65 publications
(91 reference statements)
15
136
0
Order By: Relevance
“…The idea of the interaction between radio plasma and dense ISM affecting the radio emission has indeed been proposed for high-z radio galaxies to explain e.g. the correlation between the steepness of the spectral index and the redshift of the sources (Athreya & Kapahi 1998;Klamer et al 2006). The possibility of a higher incidence of powerful radio sources associated with disk galaxies at high-z has been brought up by Norris et al (2008), although they have so far identified only one possible candidate in their deep field.…”
Section: Radio Sources Like Pks 1814-637: How Rare?mentioning
confidence: 99%
“…The idea of the interaction between radio plasma and dense ISM affecting the radio emission has indeed been proposed for high-z radio galaxies to explain e.g. the correlation between the steepness of the spectral index and the redshift of the sources (Athreya & Kapahi 1998;Klamer et al 2006). The possibility of a higher incidence of powerful radio sources associated with disk galaxies at high-z has been brought up by Norris et al (2008), although they have so far identified only one possible candidate in their deep field.…”
Section: Radio Sources Like Pks 1814-637: How Rare?mentioning
confidence: 99%
“…Miley & De Breuck 2008;Klamer et al 2006;Verkhodanov & Khabibullina 2010;Singh et al 2014), and several recent studies have failed to find a correlation between the spectral index and redshift (Ker et al 2012;Singh et al 2014;Smolčić et al 2014). The exact definition of a USS source (based on spectral index) differs between authors, e.g., α 608 MHz 327 MHz < −1.1 (Wieringa & Katgert 1992), α 4.85 GHz 151 MHz < −0.981 (Blundell et al 1998 (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extended gas disks within the radio galaxy Best (2000) pointed out that radio galaxies with very extended radio sources are particularly good candidates for being cluster central galaxies because the pressure from the Mpc-scale intracluster medium boosts the luminosity of the radio source even for comparably extended jets (see also Athreya et al 1998;Klamer et al 2006). Many authors have previously suggested that the progenitors of brightest cluster galaxies are likely to be found among HzRGs (e.g., Pentericci et al 2001;Miley et al 2006;Hatch et al 2009), andWylezalek et al (2013) find from IRAC imaging that TXS 2353-003 is even associated with the most strongly pronounced overdensity within their sample.…”
Section: Partial Agn Illumination Of Ambient Halo Cloudsmentioning
confidence: 99%